Platelet activation in atherogenesis associated with low-grade inflammation. - Antoniades, C; Bakogiannis, C; Tousoulis, D; Demosthenous, M; Marinou, K; Stefanadis, C (2010)
Further to the established role of platelets in thrombosis and hemostasis, increasing evidence suggests that they also play a crucial role in atherogenesis. Platelets produce a number of agents contributing to the systemic low-grade inflammation implicated in atherogenesis. Platelet activation following inflammatory stimulus leads to the expression of surface receptors such as GPIb/IX/V, P-selectin, CD40, and to the release of several pro-inflammatory agents. Platelet receptors and released molecules play a critical role during the initiation and the progression of atherosclerosis by mediating leukocytes recruitment and adhesion to the vascular wall. Endothelial dysfunction, an early feature in atherosclerosis, is associated with low-grade inflammation within the vascular wall, and it leads to the reduced bioavailability of nitric oxide. Dysfunctional endothelium itself releases inflammatory molecules leading toward platelets activation and adhesion to the vascular wall. Platelets are no longer considered simply as cells participating in thrombosis. They are regulators of multiple processes in the human body, including inflammation, regulation of endothelial physiology and atherogenesis. The design of new therapeutic strategies targeting platelets and their impact in atherosclerosis-related low-grade inflammation are in the center of current cardiovascular research.